2018
DOI: 10.3390/ijgi7100408
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Landscape Metrics for Three Different Level Land Cover/Land Use Maps

Abstract: This research aims to investigate how different landscape metrics are affected by the enhancement of the thematic classes in land cover/land use (LC/LU) maps. For this aim, three different LC/LU maps based on three different levels of CORINE (Coordination of Information on The Environment) nomenclature were created for the selected study area using GEOBIA (Geographic Object Based Image Analysis) techniques. First, second and third level LC/LU maps of the study area have five, thirteen and twenty-seven hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 38 publications
0
32
0
2
Order By: Relevance
“…The "Urban Field" PLAND (UFPLAND) could depict the process of urban spatial growth as diffusing or coalescing just like the PLAND (Dietzel et al, 2005). If the growth is diffusing, it is expected that there will be scattered "seeds" of centers of growth over the landscape and UFPLAND value will be low (Sertel et al, 2018). On the other hand, if the process is in a state of coalescence, urban extent will be more compact and UFPLAND value will be high (Sertel et al, 2018).…”
Section: Image Classification and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The "Urban Field" PLAND (UFPLAND) could depict the process of urban spatial growth as diffusing or coalescing just like the PLAND (Dietzel et al, 2005). If the growth is diffusing, it is expected that there will be scattered "seeds" of centers of growth over the landscape and UFPLAND value will be low (Sertel et al, 2018). On the other hand, if the process is in a state of coalescence, urban extent will be more compact and UFPLAND value will be high (Sertel et al, 2018).…”
Section: Image Classification and Analysismentioning
confidence: 99%
“…If the growth is diffusing, it is expected that there will be scattered "seeds" of centers of growth over the landscape and UFPLAND value will be low (Sertel et al, 2018). On the other hand, if the process is in a state of coalescence, urban extent will be more compact and UFPLAND value will be high (Sertel et al, 2018). The UFPLAND might not be sensitive to spatial pattern and processes within the urban field especially if the UFPLAND is low.…”
Section: Image Classification and Analysismentioning
confidence: 99%
“…Square shape window with a side length of 100 m was used, and 8-cell neighbour rule was applied for all standard analysis. The FRAGSTATS was used by several studies for understanding the configuration of the landscape 85,86 . After making the model for the year 2018, we projected the same for past decades year 1998, 2008 and also for the future year 2028.…”
Section: Model Preparation Evaluation and Change Dynamics Of Ensemblmentioning
confidence: 99%
“…For example, the single large or several small reserves problem in landscape ecology queries whether species diversity is better preserved by one large reserve or by several small reserves when the total protected area is equivalent [28]. Using identical data sources and methods, Sertel et al [29] generated three land cover maps (primary, secondary, and tertiary) and then used landscape indices analysis to compare the landscape fineness to the landscape indices. It was shown that the finer the land cover data, the more accurately the landscape features were defined.…”
Section: Introductionmentioning
confidence: 99%